Analisis Rasio Energi pada Produksi Biodiesel dengan Reaktor Berpengaduk Statik Sistem Kontinu (Energy Ratio Analysis on Biodiesel Production Using Continuous Static Mixing Reactor) - Inge Scorpi Tulliza; Armansyah Halomoan Tambunan; Edy Hartulistiyoso; Dadan Kusdiana (Jurnal Keteknikan Pertanian, 2020)
Energy ratio analysis of various methods and technology of biodiesel production is needed to get an idea of the effectiveness of the method or technology used. This study aims to analyze the energy ratio in the biodiesel production process with a continuous static mixing reactor. RE2 values for biodiesel production using a continuous static mixing reactor with catalysts 0.3% (w/w) and 0.5% (w/w), respectively are 0.94 and 1.03. The addition of the number of modules to achieve the conversion rate required in accordance with SNI-7182 (2018) can increase the energy ratio to 1.10 in the use of catalysts 0.3% (w/w), and 1.09 with the use of a 0.5% catalyst (w/w). The energy ratio value with the addition of the module is about 10% higher than the ratio value for the bacth method using a 1% catalyst and the SMV method without catalyst.